2016
DOI: 10.1002/hipo.22590
|View full text |Cite
|
Sign up to set email alerts
|

A single bout of resistance exercise improves memory consolidation and increases the expression of synaptic proteins in the hippocampus

Abstract: Over the past decade, several studies have indicated that chronic resistance exercise (i.e., strength training, weight lifting, etc.) is beneficial for brain health and cognitive function. However, little is known about the effects of a single bout of resistance exercise on brain function, particularly on memory consolidation. Therefore, the purpose of the present study is to examine the effects of a single bout of resistance exercise applied immediately after the training of fear conditioning on memory consol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 57 publications
(89 reference statements)
0
15
0
Order By: Relevance
“…Recently, a meta-analysis study reported that a single bout of moderate aerobic exercise improves inhibitory control, cognitive flexibility, and working memory in preadolescent children and older adults (Ludyga et al, 2016), indicating that beyond the well know effects of long-term exercise on the brain, acute exercise also can be used as a tool for situations demanding a high executive control. Interestingly, we and others have found that a single bout of both aerobic (Siette et al, 2014) and resistance (Fernandes et al, 2016) exercise is able to enhance memory consolidation in rats.…”
Section: Introductionmentioning
confidence: 79%
“…Recently, a meta-analysis study reported that a single bout of moderate aerobic exercise improves inhibitory control, cognitive flexibility, and working memory in preadolescent children and older adults (Ludyga et al, 2016), indicating that beyond the well know effects of long-term exercise on the brain, acute exercise also can be used as a tool for situations demanding a high executive control. Interestingly, we and others have found that a single bout of both aerobic (Siette et al, 2014) and resistance (Fernandes et al, 2016) exercise is able to enhance memory consolidation in rats.…”
Section: Introductionmentioning
confidence: 79%
“…Notably, aerobic exercise only produces changes in hippocampal IGF-1 and not IGF-1 receptor density, indicating that the latter effect may be selective to resistance modalities. These effects were not reported in a later study that used an acute training procedure (Fernandes et al 2016), suggesting that the effects of resistance exercise on IGF-1 might differ between acute and chronic regimens. Interestingly, significant and positive correlations were observed following chronic training between systemic and hippocampal IGF-1 concentrations, as well as performance in a passive avoidance task (Cassilhas et al, 2012b).…”
Section: Recent Advances In Resistance Exercise and Cns Activitymentioning
confidence: 62%
“…Similarly, resistance exercise improves spatial memory, with access to a resistance running wheel (Lee et al, 2012; Suijo et al, 2013) or regular ladder climbing with weighted loads (Cassilhas et al, 2012a) decreasing the latency and/or distance to reach a platform in a Morris water maze task (for details on this task see Ang et al, 2006; Morris et al, 1982). As described in Section 4.2, resistance training also improves associative learning as measured by fear conditioning tests (Cassilhas et al, 2012b; Fernandes et al, 2016; Kim et al, 2016). …”
Section: Recent Advances In Resistance Exercise and Cns Activitymentioning
confidence: 91%
See 1 more Smart Citation
“…Physical activity plays a key role in the prevention of disorders such as depression, cardiovascular disease, diabetes, and some types of cancer (Katz & Pate, ). Interestingly, even a single bout of either aerobic (Siette, Reichelt, & Westbrook, ) or resistance (Fernandes, Soares, do Amaral Baliego, & Arida, ) exercises enhances memory consolidation in rats. Aerobic exercise by itself or in combination with the selective serotonin re‐uptake inhibitor sertraline lowered the depressive score and relapse rate at a 6‐month follow‐up (Blumenthal et al, ).…”
Section: Introductionmentioning
confidence: 99%